Preserving the Cultural Heritage of Indonesian Society through Digital Preservation in Libraries - Ilabakho, Robertus; Rasmita, Rasmita (Knowledge Garden: International Journal of Library Studies, 2025)
Digital preservation is crucial in safeguarding Indonesia's cultural heritage by ensuring historical documents, artifacts, and traditional knowledge remain accessible for future generations. However, digitalization efforts face significant challenges related to technical infrastructure, legal frameworks, and public engagement. This study aims to analyze the role of libraries in digital preservation, identifying key benefits, challenges, and potential strategies for sustainable implementation. Using a thematic analysis approach, data was collected through an extensive literature review of 500 academic articles filtered into 16 relevant studies. The results indicate that digitalization enhances accessibility and efficiency in preserving cultural materials but is hindered by financial constraints, insufficient technological resources, and unclear legal protections. Moreover, the lack of trained professionals in digital archiving further complicates the implementation process. The findings highlight the need for stronger government policies, improved funding, and collaborative efforts among libraries, policymakers, and cultural institutions. The study recommends integrating advanced technologies such as artificial intelligence and blockchain to strengthen digital preservation strategies and ensure long-term sustainability. Additionally, hybrid approaches that merge digital and physical experiences can enhance public engagement with cultural heritage. This research contributes to the growing discourse on digital heritage conservation by providing a comprehensive analysis of current challenges and opportunities, serving as a valuable reference for stakeholders involved in cultural preservation and digital library management.